Использование методов импульсной модуляции в медицинских озонаторах - Кипенский, Андрей Владимирович; Куличенко, Вячеслав Викторович; Махонин, Николай Витальевич; Коробка, А. А. (НТУ "ХПИ", 2014)
В работе проанализированы различные способы регулирования параметров озоно-кислородной смеси в медицинских озонаторах. Показана целесообразность использования методов импульсной модуляции для регулирования концентрации озона в озоно-кислородной смеси и ее расхода. Предложена структурная схема обеспечивающая регулирование параметров озоно-кислородной смеси методом импульсной модуляции. Описан принцип формирования управляющих импульсов микропроцессорной системой импульсного управления, которая позволяет регулировать параметры ОКС методами широтно-импульсной или частотно-импульсной модуляции.

The work analyzes different ways of controlling the parameters of the ozone-oxygen mixture in medical ozone generators. For ozone in medical ozone generators are most often used electrophysical method, which consists in the creation of surround barrier discharge in the gas gap of the discharge chamber through which the pro-allowed medical oxygen. The expediency of the use of pulse modulation methods for controlling the concentration of ozone in the ozone-oxygen mixture and its flow are shows. The structural scheme provides for the regulation of parameters of ozone-oxygen mixture by pulse width modulation. The principle of formation of the control pulses microprocessor pulse control system which allows adjusting parameters of ozone-oxygen mixtureby pulse width or pulse frequency modulation methods are describes. It should be noted that the use of pulse modulation methods in medical ozone allows, first of all, to ensure accurate testing of all parameters specified ozone-oxygen mixture, as well as improves the weight and dimensions of energy management systems and material flows.
The use of pulse modulation methods in medical ozone generators
Keywords: озонотерапия; озоно-кислородная смесь; широтно-импульсная модуляция; система управления; микропроцессор; ozonetherapy; medical ozonator; ozone-oxygen mixture; pulse width modulation; control system; microprocessor